Risk of hypoglycaemia in type 2 diabetes patients under different insulin regimens: a primary care database analysis - Kostev, Karel (Ger Med Sci, 2015)
Aims: To compare rates and predictors of documented hypoglycaemia in type 2 diabetes patients treated with either basal insulin supported oral therapy (BOT), conventional therapy (CT) or supplementary insulin therapy (SIT) in primary care. Methods: Data from 10,842 anonymous patients (mean age ± SD: 54 ± 8 yrs) on BOT, 2,407 subjects (56 ± 7 yrs) on CT, and 7,480 patients (52 ± 10 yrs) using SIT from 1,198 primary care practices were retrospectively analyzed (Disease Analyzer, Germany: 01/2005–07/2013). Stepwise logistic regression (≥1 documented hypoglycaemia: ICD code) was used to evaluate risk factors of hypoglycemia. Results: The unadjusted rates (95% CI) per 100 patient-years of documented hypoglycaemia were 1.01 (0.80–1.20) (BOT), 1.68 (1.10–2.30) (CT), and 1.61 (1.30–1.90) (SIT), respectively. The odds of having ≥1 hypoglycemia was increased for CT (OR; 95% CI: 1.71; 1.13–2.58) and SIT (1.55; 1.15–2.08) (reference: BOT). Previous hypoglycemia (OR: 11.24; 6.71–18.85), duration of insulin treatment (days) (1.06; 1.05–1.07), history of transient ischemic attack (TIA)/stroke (1.91; 1.04–3.50), and former salicylate prescriptions (1.44; 1.06–1.98) also showed an increased odds of having hypoglycemia. Higher age was associated with a slightly lower odds ratio (per year: 0.98; 0.97–0.99). Conclusions: Insulin naïve type 2 diabetes patients in primary care, initiated with CT and SIT have an increased risk of hypoglycaemia compared to BOT, which is in line with previous randomized controlled trials. As hypoglycaemic events are associated with an increased mortality risk, this real-world finding is of clinical relevance.